2003
DOI: 10.1046/j.1365-2125.2003.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic analysis of meloxicam in rheumatoid arthritis patients

Abstract: Aim To perform a nonlinear mixed effect modelling (NONMEM) population pharmacokinetic analysis of meloxicam plasma concentrations in rheumatoid arthritis (RA) patients participating in three clinical trials, and to evaluate the effects of age, weight, gender and concomitant medications on meloxicam pharmacokinetics. Methods Meloxicam was administered to RA patients once daily for 3 weeks or 6 months at doses between 7.5 and 60 mg. Plasma samples were obtained at least 7 days after the first dose and meloxicam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…To date no well accepted rule exists for minimum levels of COMED in a POPPK study. Empirically some investigators include only COMEDs occurring in 5% of the population [22]. The current study confirms that lower levels of COMED can be detected using POPPK even for borderline inhibitors.…”
Section: Discussionsupporting
confidence: 89%
“…To date no well accepted rule exists for minimum levels of COMED in a POPPK study. Empirically some investigators include only COMEDs occurring in 5% of the population [22]. The current study confirms that lower levels of COMED can be detected using POPPK even for borderline inhibitors.…”
Section: Discussionsupporting
confidence: 89%
“…These data can also be extrapolated to other drugs that are mainly metabolized by hepatic CYP2C9 and have low hepatic extraction ratios. In addition, Meineke & Türck reported that body weights and age influence the CL of meloxicam, and that body weights affected the volume of distribution of meloxicam in patients with rheumatoid arthritis. However, neither body weights nor ages were statistically significant covariates for CL in the present study, whereas CYP2C9 genotype was a strong predictor of the CL of meloxicam.…”
Section: Discussionmentioning
confidence: 99%
“…Meloxicam is a cyclooxygenase inhibitor commonly used to treat patients with pain due to rheumatoid arthritis and surgery . The dose proportionality between orally administered doses of 7.5–30 mg has been confirmed, and the total clearance, volume of distribution, and absolute bioavailability have been reported to be 7.2 mL/min, 10.7 L, and 89% in healthy subjects, respectively.…”
mentioning
confidence: 96%
“…The exclusion of women from participating in the present study was due to sex-dependent differences in the PK of meloxicam, as previously reported by Meineke and Türck,14 who demonstrated that both age and sex significantly affected meloxicam clearance.…”
Section: Methodsmentioning
confidence: 79%